Maqasidic approach in the management of Waqf property: A study with reference to Malaysian contemporary issues - Abdulsoma, Thoarlim; Fauzi, Yusoh; Roslan, Ab Rahman; Ahmad Fauzi, Hassan; Mohammed Muneer'deen, Olodo Al-Shafi'i; Mohamad, Iman (2017)
In Malaysia, waqf is becoming a popular mechanism among Muslims to bequeath property to gain a reward from Allah. Hectares of waqf land given away for different purposes will certainly lead to many managerial issues. Some issues are easily resolved while others are not. Sometimes it is enough to resort to the legal provisions to solve the problems of waqf land. However, there are many other issues with no clear legal solutions as in the statutes. Without a clear statute, maqasid al-shariah (objectives of Sharia) may come into the picture to offer an alternative in addressing issues relating to waqf land. Among some of these issues is land that is donated for specific unrealistic purposes and land that cannot be developed because of lack of funding. Using the qualitative and policy-centred approaches as the method of research, this paper aims to entertain the issues by applying the principles of maqasid al-shariah. This paper examines the actual objectives behind the waqf rules (fiqh al-waqf) in Islam and those objectives will be used as the parameter and guideline to address contemporary issues relating to waqf land. The application of the said parameter can be recognised as the ‘maqasidic’ approach.